Difficulties in Emotion Regulation Among Iranian Remarried Women: The Role of Mindfulness, Thought–Action Fusion, and Emotion Regulation. Issue 2 (17th February 2019) - Jelvani, Razieh; Etemadi, Ozra; Jazayeri, Rezvanoosadat; Fatehizade, Maryam
ABSTRACT: The aim of this study was to predict remarried women's difficulties in emotion regulation through mindfulness, thought–action fusion, and emotion regulation strategies. The research method was descriptive. Two hundred and fifty-two remarried women were administered the Freiburg Mindfulness Inventory (FMI), Thought–Action Fusion Scale, Emotion Regulation Questionnaire (ERQ), and Difficulties in Emotion Regulation Scale (DERS). The data were analyzed using multiple regression. The results of the data analysis showed that thought–action fusion and suppression are positively correlated to difficulties in emotion regulation, whereas reappraisal and mindfulness were negatively related to difficulties in emotion regulation. Also, mindfulness, thought–action fusion, reappraisal, and suppression are able to predict emotion regulation difficulty. This study indicated that it is important to consider the emotion and its dysregulation among remarried women.